Pressure-controlled microfluidic sub-picoliter ultramicro-volume syringes based on integrated micro-nanostructure arrays. Issue 20 (24th September 2019) - Yu, Nianzuo; Liu, Yongshun; Wang, Shuli; Tang, Xiaoduo; Ge, Peng; Nan, Jingjie; Zhang, Junhu; Yang, Bai
Abstract : Ultramicro-volume syringes are fabricated in microchannels. The minimum of available droplet volume is in increments as low as 0.5 pL with 96% accuracy. Specifically, controllable synthesis of nanocrystals could be produced in a lab-on-chip platform. Abstract : Ultramicro-volume syringes were fabricated by integrating micro-nanostructure arrays in microchannels for quantitatively dispensing sub-picoliter volumes of liquids. Using this system, liquids were dispensed in volume increments as low as 0.5 pL with 96% accuracy. Specifically, the controllable synthesis of nanocrystals was achieved using a lab-on-chip platform that was integrated with the syringes.